A homogenized large deformation constitutive model for high temperature oxidation in fiber-reinforced polymer composites. (September 2021) - Konica, Shabnam; Sain, Trisha
Abstract: In the present work we develop a thermodynamically consistent, large deformation homogenized constitutive model to predict high-temperature oxidation in fiber-reinforced polymer matrix composites (FRPMCs). The presence of fibers introduces anisotropy in the diffusion and the chemical reactions prevailing oxidation for these composite materials, resulting in heterogeneous shrinkage and stress distribution within the representative material volume. To model such behavior, we develop a homogenized approach considering a unidirectional composite RVE as a mixture of fibers and matrix, represented by the fiber volume fractions and their respective orientations. In what follows, we develop a coupled chemo-mechanical model to predict the oxidation response of this highly anisotropic composite material, based on an earlier developed multiphysics theory of bulk polymer's oxidation. We numerically implement the proposed model in finite elements by writing a user element subroutine (UEL) in ABAQUS/Standard and perform various simulations in 2-D and 3-D composites RVE. The results demonstrate that the proposed model is capable of predicting several important characteristics of oxidation in fiber-reinforced composites, such as, preferential growth of oxide layer, heterogeneous distribution of residual stress, and the effect of fiber volume fraction on the oxidation process. Highlights: A thermodynamically consistent homogenized constitutive model for high temperature oxidation in the fiber reinforced polymer composite is proposed. The model considers the fiber induced anisotropy and the effect of volume fractions in the diffusion–reaction kinetics as well as in the large deformation kinematics. Numerical implementation and model predictions qualitatively demonstrate the preferential growth of oxide layer in the composite and the heterogeneous stress/strain distribution influenced by the presence of fibers.